Swedish Sign Language as second language corpus - Mesch, Johanna; Schönström, Krister (Stockholm University, 2020)
The Swedish Sign Language as second language corpus includes video recordings and documentation of sign language texts, produced by adult hearing second language learners of Swedish Sign Language.

Korpusen i svenskt teckenspråk som andraspråk omfattar inspelade videomaterial och dokumentation av teckenspråkstexter, producerade av vuxna hörande andraspråksinlärare.
Korpus i svenskt teckenspråk som andraspråk
Keywords: Sign Language; Teckenspråk; second language acquisition; andraspråksinlärning; Swedish Sign Language; svenskt teckenspråk; Swedish Sign Language as second language; svenskt teckenspråk som andraspråk; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; Humanities and the Arts; Humaniora och konst; Languages and Literature; Språk och litteratur